From classic models to new pathways: unraveling the anatomy and function of the inferior fronto-occipital fasciculus in language processing - Nogueira, Pedro Aleixo; Neiva, Julia Franco; Couto, Maíra Piani; Giglio, Marcus Vinicius; Maldaun, Marcos Vinicius Calfat; Joaquim, Andrei Fernandes; Ghizoni, Enrico; Formentin, Cleiton (Frontiers in Psychology, 2025)
IntroductionThis study explores the anatomy and function of the inferior fronto-occipital fasciculus (IFOF), focusing on its role in language processing. Through a comprehensive systematic review and detailed anatomical dissections, we aim to elucidate the IFOF’s anatomical organization, its contributions to language processing, and its complex three-dimensional configuration, ultimately enhancing the safety and precision of neurosurgical practices.MethodsThis study employed a two-part methodology: (1) anatomical dissections using Klinger’s technique on three human brains, which were fixed and frozen; and (2) a systematic literature review adhering to PRISMA guidelines, with a search of the EMBASE and PubMed databases on January 1, 2025, analyzing 510 studies on IFOF anatomy and function, with a focus on its role in language processing and implications for neurosurgical practice.ResultsAnatomical dissections identified the IFOF as a prominent anterior–posterior white matter tract with distinct dorsal and ventral components. The dorsal component links the pars triangularis and pars orbitalis of the frontal lobe to the superior parietal lobe and posterior occipital gyri, while the ventral component connects the inferior occipital gyrus and posterior basal temporal region to the dorsolateral prefrontal and orbitofrontal cortices. The IFOF was found to traverse through key areas, including the extreme capsule, insula, and claustrum, and was closely associated with the uncinate fasciculus. The systematic literature review included 15 studies, highlighting the IFOF’s critical role in cognitive and linguistic functions, particularly in semantic language processing, reading, naming, and integrating visual information for meaning interpretation. It plays a key role in language comprehension by connecting posterior visual regions to anterior semantic areas. The IFOF also contributes to visual attention and spatial processing, underscoring its importance in contemporary linguistic models. Damage to the IFOF can cause semantic paraphasia, reading difficulties, spatial neglect, and aphasia, highlighting its crucial role in language and cognitive functioning.ConclusionThe IFOF plays a pivotal role in integrating visual, motor, and semantic information, facilitating complex interactions between cognitive, linguistic, and visuospatial functions. Its dorsal component aids visuospatial integration, while the ventral component underpins semantic processing. The IFOF’s anatomical and functional complexity underscores its critical consideration in neurosurgical planning.